Positive Laws in Facing Revenge Porn, Are They Effective? - Ahmad Izzuddin; Dakka Fadilah M Harahap (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Revenge porn is a phenomenon that is increasingly occurring as a result of advances in information technology, especially among teenagers. This practice involves the unauthorized dissemination of one's intimate content through online media for the purpose of humiliation or as a form of revenge. Even though the Information and Electronic Transactions Law (UU ITE) and the Pornography Law are the main legal umbrellas used to overcome revenge porn cases, the effectiveness of positive law in dealing with this crime is still questionable. This research uses literature research methods to analyze and interpret the effectiveness of positive law in dealing with revenge porn in Indonesia. Results showed that despite the existence of legal tools that could be used to ensnare perpetrators, the lack of specific regulations governing online gender-based violence was a major obstacle to law enforcement. Improvement efforts are therefore needed in the existing legal system to provide better protection for victims and ensure that perpetrators can be effectively ensnared.